Організаційна структура відділу ІТ закладу охорони здоров’я - Карімов, Геннадій Іванович; Karimov, Hennadii; Карімов, Іван Кабіденович; Karimov, Ivan; Нужна, Світлана Анатоліївна; Nuzhna, Svitlana; Булай, Олександр Юрійович; Bulai, Oleksandr (Дніпровський державний технічний університет, 2024)
У роботі розглядається проблема дослідження організаційної структури відділу ІТ закладу охорони здоров’я. Підключення закладу охорони здоров'я до Електронної системи охорони здоров’я є однією з обов’язкових умов Міністерства охорони здоров'я України що, у свою чергу, потребує значної кількості комп’ютерної техніки яка постійно використовує комунікаційні технології та працює із значним обсягом інформації (бази даних). Штатна робота всієї сукупності вимагає участі відповідного фахівця, а, враховуючи масштаби закладу – відповідного структурного підрозділу, який відповідає за роботу комп’ютерної техніки та інформаційних технологій.. У підсумку, запропонована організаційна структура відділу ІТ закладу охорони здоров’я в який, роль фахівця відділу IT витікає з загальної ролі відділку у прив’язці до закріпленого відділення. The paper considers the problem of studying the organizational structure of the IT department of a healthcare institution. Connecting a healthcare institution to the Electronic Healthcare System is one of the mandatory conditions of the Ministry of Health of Ukraine for concluding agreements with the National Health Service of Ukraine and transitioning to cavitation, which, in turn, requires a significant amount of computer equipment that constantly uses communication technologies and works with a significant amount of information (databases). The regular work of the entire complex requires the participation of a relevant specialist, and, given the scale of the institution, a relevant structural unit responsible for the work of computer equipment and information technologies (IT services). Given the current organizational structure of the institution, it is proposed to subordinate the department to the Deputy Director General. The head of the department is responsible for the system's performance within the functional scope of the Director General and his deputies and manages the specialists of the department. Each of the specialists is responsible for the functioning of the system within the assigned department. Such a functional division allows to clearly defining the areas of responsibility of each employee. The planned organizational structure of the IT service is divided into functional and support parts. The functional part ensures the functioning of the information system within the main departments and auxiliary services and consists of relevant specialists assigned to the structural unit. The support part is responsible for the operation of the information system of the institution as a whole, the administrative and economic complex and carries out general administration and current technical maintenance of the information system of the healthcare institution. The paper proposes an organizational structure of the IT department of a healthcare institution, the functional content of which depends on a specific medical information system from the list of recommended by the Ministry of Health. The possibilities of assessing the efficiency of the department and effective indicators are determined. The directions of further research into the process of digitalization of the activities of healthcare institutions are outlined
Organizational structure of the it department the institution care of health
Keywords: організаційна структура; organizational structure; ІТ; ІТ; заклад охорони здоров’я; the institution care of health; електронна система; electronic system; функціональний розподіл; functional distribution